THE ROLE OF PROFITABILITY, CAPITAL STRUCTURE AND FIRM SIZE TOWARDS THE FIRM VALUE OF PT. CITRA MARGA NUSAPHALA PERSADA, TBK DURING PERIOD 1995-2017 - Yusuf, Julio; Dewi Syarif, Andam (Dinasti International Journal of Economics, Finance & Accounting, 2021)
This research has intend to reveal and investigate the impact of return on assets, return on equity, debt equity ratio, and firm size towards firm value of PT. Citra Marga Nusaphala Persada Tbk. The research Sampling used a quantitative approach. The Samples obtained and used were financial Statements of PT CMPN Tbk which have been published on the IDX with an observation period of 23 years with 2 semesters of each year. These research data used was secondary data through time series data analysis method. The results of this research shows that return on assets has a negative and significant affect on firm value; return on equity has a positive and significant affect on firm value; debt equity ratio has a negative and significant affect on firm value; firm size has no significant affect on firm value.